A passion for success : - Inamori, Kazuo (McGraw-Hill, 1995)
Written in the distinguished tradition of Tao of Leadership, this guide is an ideal fusion of inspiration and incomparable business genius, revealing an approach to wisdom and success considered revolutionary and refreshing even in Japan. Each of its key principles for the enrichment of business and personal life is supported by anecdotes drawn from Dr. Inamori's vast experiece.